Enhanced Optical Nonlinearities in All-Dielectric Metasurfaces - Vabishchevich, P. P.; Vaskin, A.; Addamane, S.; Karl, N.; Liu, S.; Sharma, A. P.; Balakrishnan, G.; Reno, J. L.; Keeler, G. A.; Sinclair, M. B.; Staude, I.; Brener, Igal (Optics InfoBase Conference Papers, 2019)
We experimentally demonstrate simultaneous generation of second-, third-, fourthharmonic, sum-frequency, four-wave mixing and six-wave mixing processes in III-V semiconductor metasurfaces and show how to tailor second harmonic generation to zerodiffraction order via crystal orientation.
CRIS-Team Scopus Importer:2023-04-20